Phylogenetic analysis of the Archaeocidaridae and Palaeozoic Miocidaridae (Echinodermata, Echinoidea) and the origin of crown group echinoids. (6th September 2019) - Thompson, Jeffrey R.; Mirantsev, Georgy V.; Petsios, Elizabeth; Bottjer, David J.
Abstract: The archaeocidarids comprise the most derived stem group echinoids and have long been regarded as closely related to the crown group. The fossil record of echinoids in the Palaeozoic is, however, poor, so details surrounding the initial divergence of crown group echinoids are not well constrained. In order to better understand the phylogenetic relationships of the most derived stem group and most basal crown group echinoids, a phylogenetic analysis was undertaken of the Archaeocidaridae, including the genera Nortonechinus, Devonocidaris, Lepidocidaris, Polytaxicidaris and Archaeocidaris and the Palaeozoic miocidarid cidaroids from the genus Eotiaris . We found that Archaeocidaris appears to be paraphyletic with respect to crown group echinoids. Furthermore, we mapped character evolution along our phylogeny and found that the diversification of archaeocidarids and miocidarids may be linked to large‐scale macroecological changes taking place in the late Palaeozoic, including increasing predation pressure and echinoid encrustation by epibionts. We compared the stratigraphical distribution of archaeocidarid and miocidarid occurrences to our resulting phylogenies, and found that the fit of our cladograms to the stratigraphic record of archaeocidarid occurrences is worse than other echinoid groups, supporting the idea that the imbricate plated archaeocidarids have a poor fossil record. In the course of carrying out these analyses, we also felt it necessary to describe a new species of Archaeocidaris, Archaeocidaris ivanovi sp. nov. We also provide novel descriptions and interpretations for Devonocidaris primaevus, Archaeocidaris brownwoodensis, Archaeocidaris apheles and revise the synonymy of Archaeocidaris legrandensis and ? Eotiaris meurevillensis, which may be a crown group echinoid.